The Misguided Beliefs of Financial Advisors - LINNAINMAA, JUHANI T.; MELZER, BRIAN T.; PREVITERO, ALESSANDRO (Journal of Finance, 2021)
ABSTRACT A common view of retail finance is that conflicts of interest contribute to the high cost of advice. Within a large sample of Canadian financial advisors and their clients, however, we show that advisors typically invest personally just as they advise their clients. Advisors trade frequently, chase returns, prefer expensive and actively managed funds, and underdiversify. Advisors' net returns of −3% per year are similar to their clients' net returns. Advisors do not strategically hold expensive portfolios only to convince clients to do the same; they continue to do so after they leave the industry.